Application Of Super Encryption Using Rot 13 Algorithm Method and Algorithm Beaufort Cipher For Image Security Digital - AYUDEVIAPERTIWI; Achmad Fauzi; Siswan Syahputra (Yayasan Kita Menulis, 2023)
Digital image security is becoming increasingly critical in today's digital era, where sensitive information and data are often stored in image form. Therefore, an effective and secure encryption method is needed to protect the integrity and confidentiality of digital images. This study aims to implement a stronger security approach by combining classic encryption methods, namely the ROT13 algorithm and the Beaufort Cipher algorithm which produces an encryption called